2012
DOI: 10.1182/blood-2012-02-407684
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of rabbit antithymocyte globulin and cyclosporine for aplastic anemia from the EBMT Severe Aplastic Anaemia Working Party

Abstract: Rabbit antithymocyte globulin (rATG; thymoglobulin, Genzyme) in combination with cyclosporine, as first-line immunosuppressive therapy, was evaluated prospectively in a multicenter, European, phase 2 pilot study, in 35 patients with aplastic anemia. Results were compared with 105 age-and disease severitymatched patients from the European Blood and Marrow Transplant registry, treated with horse ATG (hATG; lymphoglobulin) and cyclosporine. The primary end point was response at 6 months. At 3 months, no patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
140
4
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(159 citation statements)
references
References 33 publications
12
140
4
3
Order By: Relevance
“…36 However, in some countries (such as Brazil), rabbit ATG is the only formulation of ATG that is commercially available, which has been associated with inferior outcomes compared with horse ATG in comparative studies as first-line therapy, resulting in a greater number patients in need of salvage therapies. 37,38 The use of alternative donors as first salvage in younger patients with regimens including alemtuzumab is associated with excellent outcomes in retrospective studies. 39,40 However, for those who lack a histocompatible donor (related or unrelated) and are eligible for HSCT, investigating a haploidentical source of HSCs with post-transplantation Cy in a clinical research protocol is reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…36 However, in some countries (such as Brazil), rabbit ATG is the only formulation of ATG that is commercially available, which has been associated with inferior outcomes compared with horse ATG in comparative studies as first-line therapy, resulting in a greater number patients in need of salvage therapies. 37,38 The use of alternative donors as first salvage in younger patients with regimens including alemtuzumab is associated with excellent outcomes in retrospective studies. 39,40 However, for those who lack a histocompatible donor (related or unrelated) and are eligible for HSCT, investigating a haploidentical source of HSCs with post-transplantation Cy in a clinical research protocol is reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…(ClinicalTrial.gov identifiers: NCT00662090) Comparison of horse and rabbit antithymocyte globulin in immunosuppressive therapy for refractory cytopenia of childhood 16 In addition, a number of non-randomized studies showed inferior results for rabbit-ATG in adults and children with aplastic anemia. [17][18][19] No published series of patients with aplastic anemia has shown that rabbit-ATG is superior to horse-ATG in the context of first-line IST. [16][17][18][19][20][21][22] To date, there have only been a few reports on the efficacy of IST with rabbit-ATG in patients with MDS.…”
mentioning
confidence: 99%
“…[17][18][19] No published series of patients with aplastic anemia has shown that rabbit-ATG is superior to horse-ATG in the context of first-line IST. [16][17][18][19][20][21][22] To date, there have only been a few reports on the efficacy of IST with rabbit-ATG in patients with MDS. 10,23,24 In this study, we compared the outcome of IST using horse-ATG with that of IST using rabbit-ATG in a large series of children with RCC.…”
mentioning
confidence: 99%
“…Thus so far, none of the seven published studies comparing horse ATG and rabbit ATG has demonstrated superiority of rabbit ATG. [5][6][7][8][9][10][11] In five, rabbit ATG led to inferior overall survival or response rates [5][6][7]9,10 and in the other two 8,11 there was no significant difference between the two preparations. …”
mentioning
confidence: 99%